A Dél-Dunántúl középfokú vonzáskörzeteinek területi rendje (Egy felmérés eredményei és tanulságai a vonzáskörzet-kutatások szempontjából) - Hajdú, Zoltán (Tér és Társadalom, 1994)
From 876 settlement self governments of South Transdanubia (Baranya, Somogy, Tolna, Zala) 378 (43.2%) filled out the questionnaire about the inner catchment area organisation of the region. The questionnaire and the answers given included the evaluation of the administrative, educational, trade, financial, personal service, heath care, productive connections, the definition of the centres of the catchment areas. In South Transdanubia it is usually the towns that have functions of seat administration of medium-level catchment areas – though not in totality – , the medium-level catchment areas arc historically determined many times. The medium-level catchment areas do not form closed spatial units, most of the catchment areas have so-called "perforated" space. It is especially the bigger, functionally more developed county seats whose attraction reaches into the catchment areas of other towns. The medium-level catchment areas reach over the borders of both the county and the "region".